Implicative Intuitive Learning Media for Students Based on Broojek Business Concept - Samas Adimisa Mishbah Habibie; Ardhi Islamudin; Ellyzabeth Putri Vizandra; Ni Putu Rekha Puspita (PT FORMOSA CENDEKIA GLOBAL, 2025)
The intuitive learning media development program based on the business concept “Broojek” aims to increase students' practical understanding in facing the challenges of the digital economy through direct experience in community service. An intuitive approach, students not only gain theory but also field experience that hones critical thinking skills, business intuition, and analytical abilities. The results of this program show that an intuitive and practical approach can improve students' readiness to face real economic challenges and has the potential to become a sustainable learning model in higher education in economics and business.